ANALYSIS OF THE SPREAD OF COVID 19 IN THE FAMILY-BASED CHILD POPULATION IN KUPANG CITY IN 2022 - Fransiskus Salesius Onggang; Bringiwatty Batbual; Aben BYH Romana; Emiliandry FT Banase (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
COVID-19 is an infectious disease from an infected person carrying the virus to people who are susceptible to contracting it. The role of the family in preventing the spread of the epidemic. Families are at the forefront to break the chain of the spread of the COVID-19 outbreak. method. using a survey method with a cross-sectional design to identify the relationship between the level of family knowledge and the effectiveness of the covid 19 vaccination. Results. . In the implementation of prevention of covid 19, as many as 355 family heads with a percentage of 64.50% implement the protocol for preventing covid 19. There are still many parents who have not vaccinated 308 families (56%). The level of sufficient knowledge is 51% with a total of 280 families. The Kupang City government's commitment to preventing covid 19 in children is mostly due to several things, including the point of administering vaccinations that is not accessible to the public as many as 208 heads with a result of 67%. Conclusion. Based on these results, it can be concluded that there is a significant influence on the level of knowledge on the effectiveness of the covid 19 vaccination at the Kupang City Health Center in 2022. The behavioral factors of parents, the level of knowledge of covid 19 transmission in children, covid 19 vaccination in parents, and maintaining health protocols have a very significant impact. transmission of the coronavirus to children who live at home with their parents.